Kepemimpinan Kepala Desa Secara Demokratis Terhadap Kinerja Aparat Desa : Penelitian - Argentina BR Keliat; Friska Noptantia; Incik Amirah Zuhrati Haya; Rotua Sahat P Simanullang (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Village head leadership plays a crucial role in shaping the performance quality of village officials. Democratic leadership emphasizes participation, openness, and two-way communication between the leader and subordinates. This study aims to identify how democratic village head leadership can improve village officials’ performance, particularly in discipline, responsibility, and work effectiveness. The research uses a literature review method based on relevant primary and secondary sources. The results show that democratic leadership enhances participation, strengthens coordination among village staff, and creates a harmonious and productive work environment. Therefore, democratic leadership can serve as an ideal model for improving local governance management systems in Indonesia.